Penegakan Hukum Terhadap Tindak Pidana Penadahan Kendaraan Di Kota Gorontalo - Feelix Ramadhan Tangkilisan; Umar P; Nur Insani (Fakultas Hukum Universitas Ichsan Gorontalo, 2025)
This study aims to (1) determine how law enforcement efforts are implemented against the theft of four-wheeled and two-wheeled vehicles in Gorontalo City, and (2) analyze the factors influencing the number of vehicle theft cases, specifically in 2024, which experienced the highest increase in such cases compared to the previous year. It employs an empirical legal study methodology, involving observations at the Gorontalo City Resort Police and the Gorontalo District Court. Data collection is through interviews with investigators from the Gorontalo City Resort Police and junior legal clerks, who served as participants in the study. The findings reveal that law enforcement efforts against vehicle theft in Gorontalo City have been carried out under legal provisions and the Criminal Code. However, several factors have contributed to the increase in vehicle theft cases over three years, particularly in 2024. Economic factors seem to drive individuals to engage in vehicle theft. Additionally, environmental factors, technological developments, and certain legal aspects indicate that current law enforcement measures have not yet deterred offenders effectively. This study recommends enhancing cooperation between the community and law enforcement agencies to improve oversight of vehicle theft in Gorontalo City. Furthermore, legal counseling is necessary to educate the public on the importance of avoiding involvement in vehicle theft cases